A Discourse Analysis of First and Second Thessalonians : The Relationship between Two Authentic Pauline Letters - Kim, Sungmin, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
Applying discourse analysis within the framework of Systemic Functional Linguistics (SFL), this study offers a fresh reexamination of the textual and contextual relationship between First and Second Thessalonians. Through register analysis, it uncovers a unified linguistic profile across both letters-marked by pastoral consistency, relational coherence, and structural clarity. Challenging traditional assumptions of textual and situational divergence, it provides a linguistically grounded reassessment of Pauline authorship. With a methodologically rigorous yet accessible approach, this study invites readers in New Testament studies, biblical linguistics, and early Christian discourse to revisit these foundational letters-textually, contextually, and with renewed insight.